2022
DOI: 10.1111/1759-7714.14366
|View full text |Cite|
|
Sign up to set email alerts
|

Epiplakin1 promotes the progression of esophageal squamous cell carcinoma by activating the PI3K‐AKT signaling pathway

Abstract: Background Epiplakin1 (EPPK1) has been associated with disease progression and unfavorable prognosis of many cancers, but its functional involvement in esophageal squamous cell carcinoma (ESCC) remains to be uncovered. Methods The Quantitative Real‐time PCR (qPCR) assay was employed to determine the expression of EPPK1 in ESCC tissues and cells. CCK‐8 assay, colony forming assay, wound healing assay, and transwell invasion assay were utilized to evaluate the effects of EPPK1 on cell proliferation, migration, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
3
5
0
Order By: Relevance
“…Regarding EPPK1 , epiplakin1, it is generally known to participate in epidermal growth factor signaling and cell proliferation, as well as cytoskeleton reorganization. Our data showed that EPPK1 expression is associated with short survival, which is partially coherent with previous studies that have shown that EPPK1 expression activates cell proliferation in cervical cancer and esophageal squamous cell carcinoma [ 32 , 33 ]. As for RHOD , ras homolog family member D, our study showed that RHOD expression is associated with short survival, which is partially in accord with a previous study that reported that the RHOD promotor was differentially methylated between pituitary adenoma and normal tissue [ 34 ].…”
Section: Discussionsupporting
confidence: 92%
“…Regarding EPPK1 , epiplakin1, it is generally known to participate in epidermal growth factor signaling and cell proliferation, as well as cytoskeleton reorganization. Our data showed that EPPK1 expression is associated with short survival, which is partially coherent with previous studies that have shown that EPPK1 expression activates cell proliferation in cervical cancer and esophageal squamous cell carcinoma [ 32 , 33 ]. As for RHOD , ras homolog family member D, our study showed that RHOD expression is associated with short survival, which is partially in accord with a previous study that reported that the RHOD promotor was differentially methylated between pituitary adenoma and normal tissue [ 34 ].…”
Section: Discussionsupporting
confidence: 92%
“…EPPK1 was reported to be expressed in diverse developmental, progenitor, and regenerative cells, expressly in cervical and bladder cancer cells, 18,20 suggesting that EPPK1 might be a potent regulatory factor in malignancy progression. Furthermore, the abnormally expressed EPPK1 was also verified in esophageal squamous cell carcinoma 22 . In this research, the data demonstrated that EPPK1 was boosted in esophageal cancer tissues and cells.…”
Section: Discussionsupporting
confidence: 56%
“…Furthermore, the abnormally expressed EPPK1 was also verified in esophageal squamous cell carcinoma. 22 In this research, the data demonstrated that EPPK1 was boosted in esophageal cancer tissues and cells. METTL3 could interact with EPPK1 and regulate its expression via m6A modification in esophageal cancer cells.…”
Section: Mettl3 Deficiency Inhibited the Pi3k/akt Pathway By Regulati...mentioning
confidence: 62%
See 2 more Smart Citations